Proteomics characterization of Staphylococcus spp. from goat mastitis and phenogeno-typical assessment of resistance to beta-lactamics - Camila S. Pereira; Lídia M.M. Santos; Leandro S. Machado; Dayanne A. Melo; Shana M.O. Coelho; Virginia L.A. Pereira; Miliane M.S. Souza; Elmiro R. Nascimento (Pesquisa Veterinária Brasileira, 2021)
ABSTRACT: Mastitis occupies a prominent place among the diseases that affect dairy herds due to economic problems and public health. Staphylococcus spp. are infectious agents more involved in the etiology of caprine mastites, especially coagulase-negative Staphylococcus. Nineteen isolates of Staphylococcus spp. were obtained from subclinical caprine mastitis. All isolates were characterized by MALDI-TOF MS, being 47.36% (9/19) identified for S. epidermidis, 15.78% (3/19) for S. warneri, 10.52% (2/19) for S. aureus and S. caprae and 5.26% (1/19) for S. lugdunensis, S. simulans, and S. cohnii. All isolates characterized by MALDI-TOF were subjected a to polymerase chain reaction (PCR) for the 16S rRNA gene of Staphylococcus spp. to confirm the gender. After determining the species, tests for phenotypic detection of resistance to beta-lactams were carried out simple disk diffusion oxacillin, cefoxitin, penicillin G and amoxicillin + clavulanic acid, agar “screen” oxacillin and microdilution (MIC) cefoxitin. The disk diffusion test showed a strength of 58% (11/19) for penicillin G, 26.31% (5/19) for cefoxitin and 26.31% (5/19) for oxacillin. All strains were susceptible to amoxicillin + clavulanic acid and agar “screen” oxacillin. In the MIC, 63.15% (12/19) of the samples were cefoxitin resistant (MIC >4.0μg/ml). Then isolates were subjected to detection of the mecA resistance genes and regulators (mecl and mecRI), mecC and blaZ. Two samples of Staphylococcus epidermidis had the mecA gene. All isolates were negative for the mecA gene variant, mecl, mecRI, mecC and blaZ. These findings reinforce the importance of this group of microorganisms in the etiology of subclinical mastitis in goats and open perspectives for future research to investigate the epidemiology of the disease.